A byte for a byte. (Economist, 2013)
An editorial is presented on computer and Internet security and cyber crimes against corporations, expressing concern about the strategy of companies hacking back, or using computer-hacking tactics to retaliate against cyber-criminals and/or to retrieve their stolen data. Topics include the frequency of cyberattacks against corporations, intellectual property theft, and the U.S.'s diplomatic efforts to reduce cyberattacks originating in Russia and China.